2023
DOI: 10.3389/fcell.2023.1133680
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-assisted diagnosis of ocular surface diseases

Abstract: With the rapid development of computer technology, the application of artificial intelligence (AI) in ophthalmology research has gained prominence in modern medicine. Artificial intelligence-related research in ophthalmology previously focused on the screening and diagnosis of fundus diseases, particularly diabetic retinopathy, age-related macular degeneration, and glaucoma. Since fundus images are relatively fixed, their standards are easy to unify. Artificial intelligence research related to ocular surface d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 152 publications
(130 reference statements)
0
5
0
Order By: Relevance
“…The applications of artificial intelligence in health care are now a reality due to the advancement of computational power, refinement of learning algorithms and architectures, availability of big data and easy accessibility to deep neural networks by the public [41][42][43]. Deep learning algorithm mostly uses multimedia data (images, videos and sounds) and involves the application of large-scale neural networks such as artificial neural network (ANN), convolutional neural network (CNN) and recurrent neural network (RNN) [42]. The advantage of deep CNNs is learning the feature representation from data without human knowledge and the capability of processing large training data with high dimensionality [44].…”
Section: Artificial Intelligence -Deep Learning Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The applications of artificial intelligence in health care are now a reality due to the advancement of computational power, refinement of learning algorithms and architectures, availability of big data and easy accessibility to deep neural networks by the public [41][42][43]. Deep learning algorithm mostly uses multimedia data (images, videos and sounds) and involves the application of large-scale neural networks such as artificial neural network (ANN), convolutional neural network (CNN) and recurrent neural network (RNN) [42]. The advantage of deep CNNs is learning the feature representation from data without human knowledge and the capability of processing large training data with high dimensionality [44].…”
Section: Artificial Intelligence -Deep Learning Methodsmentioning
confidence: 99%
“…For infectious keratitis, the use of DL with CNNs has shown to potentially be a more accessible diagnostic method via image recognition [4,45,46]. Many studies have evaluated DL methods for diagnosing IK using images taken with a handheld camara, camara mounted on a slit-lamp, or confocal microscopy [42,45,[47][48][49][50][51][52][53][54][55]. Several extremely efficient DL algorithms include RestNet-152 [56], DenseNet-169 [57], Mobile-Net V2 [58], and VGG-19_BN [59].…”
Section: Artificial Intelligence -Deep Learning Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Arturo Montejo [71], an n-gram model is a type of probabilistic model that allows for statistical prediction [72] of the next element in a sequence of elements observed up to that point. An n-gram model can be defined as a Markov chain of order n-1 [73].…”
Section: Rq2: What Are the Most Commonly Used Topics In Research On A...mentioning
confidence: 99%
“…There are four main approaches to screening patients for glaucoma: measuring IOP, examining the angle anatomy, evaluating the visual field (VF) and assessing optic nerve head (ONH) and nerve fiber layer (RNFL) [18][19] . Currently, AI is commonly used in glaucoma management including IOP, VF, false positive (FP), and OCT [20] . A prospective cross-sectional study demonstrated that automated IOP measurements using DL of Goldmann applanation tonometry (GAT) videos is comparable to standard GAT [21] .…”
Section: Introductionmentioning
confidence: 99%